Auditoria de Gestión para la empresa Tealvid. - Viñamagua Cuenca, Mercy Rocio (2014)
The present application of the audit of negotiation establishes a methodology to follow to know the quality of efficiency in each one of the areas of the enterprise. I have taken as a particular case the enterprise TEALVID, dedicated to the business in its three areas that make it. TEALVID has more than 10 years in the market and it has never performed any audit in the enterprise, by the same they are happy to know the efficient way to automate each one of the process that make the areas of the enterprise because there is any shortcomings that influence to give a good performance in all the areas that make it, causing administrative costs and expenses by present in late way the financial information to its respective organism regulators. It is required to verify the negotiation of each one of the areas of the enterprise because it does not know with certainly the shortcomings existing, neither the strengths with they have. Only knowing the best negotiation of the enterprise we can leave established a solid structure in order to be accomplished for the human talent in their totality.